Improved the performance of enhancement operators for noisy image - Anwar, Dalya Abdullah (International Journal of Psychosocial Rehabilitation, 2020)
Edge detection is a procedure of figuring out and locating sharp discontinuities in an image. The cause for this is that edges form the define of an object and it’s far the boundary among an item and the tradition. The aim of this research is to improve the performance of enhancement operators for noisy image, and to highlight these limits with the help of the MATLAB program and Gabor filter. The results were reported as the Gabor filters are involved with the indication, ensuing in so it is referred to as Gabor area, its benefits is Gabor feature where is a suitable fit to the receptive field weight functions. The Gabor filter could be very useful in photo processing programs the use of aspect detection. In case of human essences Gabor filter offers better effect as the chosen factors generate the large scale and sunnier intensity of the edges. Though, this filtering stage does not give appropriate shapes of piece but it generates exclusive shapes for special object faces and generate thicker edges as reviewed.